Flowerlike Tin Diselenide Hexagonal Nanosheets for High-Performance Lithium-Ion Batteries - Yu, Qiyao; Wang, Bo; Wang, Jian; Hu, Sisi; Hu, Jun; Li, Ying (Frontiers in Chemistry, 2020)
SnSe2 nanosheet is a common anode for lithium-ion batteries (LIBs), but its severe agglomeration hinders its practical application. Herein, a three-dimensional (3D) SnSe2 nanoflower (F-SnSe2) composed of non-stacking vertical upward hexagonal nanosheets was prepared through a colloidal method as an anode material for LIBs. Benefiting from the advantages of fast reaction-diffusion kinetics and buffering unavoidable volume variation during cycling, the F-SnSe2 electrode displays remarkable specific capacity of 795 mAh g−1 after 100 cycles at 100 mA g−1 and superior rate performance (282 mAh g−1 at 2,000 mA g−1). This work provides an effective way to get non-stacking nanosheets in energy storage field.